Non-perfusing cardiac rhythms in asphyxiated newborn piglets - Solevåg, Anne Lee (PLoS One, 2019)
AIM: We recently demonstrated that asphyxiated piglets commonly had bradycardia displayed on electrocardiography (ECG) while no carotid blood flow (CBF) or audible heart sounds could be detected. Such pulseless electrical activity (PEA) in newborn infants has not previously been thoroughly described. The aim of this study was to further investigate the occurrence of non-perfusing cardiac rhythms in asphyxiated piglets and the potential implications for the success of cardiopulmonary resuscitation (CPR) and short-term survival. METHODS: Neonatal piglets (1–4 days, 1.7–2.4kg) had their right common carotid artery exposed and enclosed with a real-time ultrasonic flow probe. Heart rate (HR) was continuously measured and recorded using ECG. This allowed simultaneous monitoring of HR via ECG and CBF. The piglets were asphyxiated until cardiac arrest, defined as no CBF and no audible beat upon precordial auscultation. CPR was performed until return of spontaneous circulation (ROSC, defined as a HR ≥100 bpm). ECG traces were retrospectively assessed. RESULTS: Nine out of 21 piglets (43%) had QRS-complexes on their ECG while no CBF and no audible heart sounds could be detected. Five (56%) of the piglets with PEA and 12/12 (100%) piglets with asystole at cardiac arrest obtained ROSC (p = 0.02). Thirty-three per cent of the piglets with PEA versus 58% with asystole survived to 4 hours post-ROSC (p = 0.39). CONCLUSION: Cardiac arrest in the presence of a non-perfusing cardiac rhythm on ECG is common in asphyxiated piglets. Clinical arrest in the presence of a non-perfusing cardiac rhythm on ECG may reduce the success of CPR.